Animal Thinking : Contemporary Issues in Comparative Cognition - Fischer, Julia, 1966-; Menzel, Randolf, 1940- (Book collections on Project MUSE., 2016)
Do animals have cognitive maps? Do they possess knowledge? Do they plan for the future? Do they understand that others have mental lives of their own? This volume provides a state-of-the-art assessment of animal cognition, with experts from psychology, neuroscience, philosophy, ecology, and evolutionary biology addressing these questions in an integrative fashion.